Risk and return implications of American depository receipts listings. - Chia, Kelvin Zhi Ling. (2008)
This paper examines the behaviour of stock returns and volatility patterns upon the listing of ADRs by Singapore firms. The sample reveals evidence showing negative post-listing abnormal returns and risk reducing effects although changes in volatilities upon the listing of the ADRs are insignificant.